2021
DOI: 10.3389/fpls.2021.770398
|View full text |Cite
|
Sign up to set email alerts
|

Theanine Improves Salt Stress Tolerance via Modulating Redox Homeostasis in Tea Plants (Camellia sinensis L.)

Abstract: Theanine, a unique non-proteinogenic amino acid, is one of the most abundant secondary metabolites in tea. Its content largely determines green tea quality and price. However, its physiological roles in tea plants remain largely unknown. Here, we showed that salt stress significantly increased the accumulation of glutamate, glutamine, alanine, proline, and γ-aminobutyric acid, as well as theanine, in the new shoots of tea plants. We further found that salt stress induced the expression of theanine biosynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Recent studies have reported that the content of theanine decreases during withering, and salt stress could induce theanine accumulation (Chen et al, 2020, 2021; Deng et al, 2012). In this study, it was verified that the content of theanine decreases by activating CsGGT2 during deionized water treatment, and salt stress could inhibit theanine hydrolysis by inhibiting CsGGT2 and enhance the resistance to salt stress in new shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the content of theanine decreases during withering, and salt stress could induce theanine accumulation (Chen et al, 2020, 2021; Deng et al, 2012). In this study, it was verified that the content of theanine decreases by activating CsGGT2 during deionized water treatment, and salt stress could inhibit theanine hydrolysis by inhibiting CsGGT2 and enhance the resistance to salt stress in new shoots.…”
Section: Discussionmentioning
confidence: 99%
“…3 , Additional file 2 : Table S1 and Additional file 3 : Table S2). Amino acids, such as l -theanine and l -proline, are compatible substances that protect plants against stress [ 51 ]. Cd indeed markedly increased l -theanine, l -histidine, and l -proline levels in the roots and leaves (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S6, Additional file 2 : Table S1 and Additional file 3 : Table S2). Chen et al [ 51 ] demonstrated that theanine plants confer salt stress tolerance by regulating redox homeostasis. We also found that l -theanine was induced by Cd stress, and its manner of affecting Cd stress is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, theanine was found to have a positive role in salt stress resistance in the shoot of tea plants by modulating H 2 O 2 accumulation [ 35 ]. In this study, exogenous theanine changed gene expression in roots, and especially altered genes encoding proteins related to extracellular region/apoplast, oxidoreductase activity, oxidation–reduction process, and H 2 O 2 metabolic process ( Fig.…”
Section: Discussionmentioning
confidence: 99%